Aplikasi Met.ode Sin.gle In.dex dal.am Pembentukan Port.ofolio Opt.imal da.ri Indeks Sah.am LQ – 45 - Muhammad Hafizh Ekaputra; Media Rosha (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — Investment is the activity of placing a number of funds at the present time with the aim of obtaining future benefits. The problem faced by investors is determining which stocks to choose in order to get maximum profit. Steps taken in order to get maximum profit is to form an optimal portfolio. T.he pu.rpose of th.is st.udy is to fo.rm an optimal portfolio of stocks incorporated in LQ-45 in the period August 2018 - July 2019 and determine the proportion of funds for each member of the opti.mal port.folio for.med using the sin.gle ind.ex met.hod. This study uses secondary data obtained from Yahoo Finance and Bank Indonesia. Purposive sampling is the sampling technique used. There are 41 stocks that still survive du.ring the obser.vation per.iod. The results of the analysis obtained from 41 LQ-45 stocks are that there are four stocks that are included in the optimal portfolio, namely; ADHI, EXCL, MNCN and TLKM with each proportion of funds of 4.081944%, 9.9706955%, 3.1884027%, and 82.7589578%. Keywords — investation, portofolio, single index method